2017
DOI: 10.1515/pielxxiw-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and health related lifestyle among nursing students

Abstract: StreSzczeniekompetencje zdrowotne i zdrowy tryb życia wśród Studentów pielęgniarStwa Wprowadzenie. Studenci pielęgniarstwa stanowią istotną populację osób do zgłębiania wiedzy dotyczącej kompetencji zdrowotnych oraz zachowań prozdrowotnych. Z jednej strony jest to grupa młodych dorosłych rozpoczynających samodzielną troskę o wlasne zdrowie, a z drugiej, uczą się oni by być profesjonalistami, którzy będą przekazywać wsparcie i wiedzę ludziom poprzez zmianę ich stylu życia dążąc do zachowania ich zdrowia lub wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In our study, there was a positive significant relationship between the HL of students and subscales of healthy lifestyle behaviours. Consistently, myriad studies showed the relationship between HL and HPLBs (Kolnik, Hozjan, & Babnik, ; Vozikis et al, ). Regression analysis results also support these findings.…”
Section: Discussionmentioning
confidence: 64%
“…In our study, there was a positive significant relationship between the HL of students and subscales of healthy lifestyle behaviours. Consistently, myriad studies showed the relationship between HL and HPLBs (Kolnik, Hozjan, & Babnik, ; Vozikis et al, ). Regression analysis results also support these findings.…”
Section: Discussionmentioning
confidence: 64%
“…This is a higher percentage than found in many other studies, 69 %( n = 52) of the nursing students had adequate health literacy knowledge [29] 50% (n = 808) of the students had adequate health literacy levels [26]. Other studies had even lower health literacy levels; 41.7% (n = 283) [31]; 37.3% (n = 337) of the nursing students had adequate health literacy [25], 31.35% (n = 160) of students had acceptable health literacy levels. The high health literacy levels in this study could suggest that the curriculum is adequately equipping nursing students with health literacy knowledge.…”
Section: Health Literacy Levelmentioning
confidence: 66%
“…Other studies revealed that the health literacy levels of nursing students were not adequate [18,28]. One study investigated the health literacy and behaviour related to health among nursing students and their results indicated that only 37.3% (n = 337 of the respondents had adequate health literacy [25]. The study reported that health literacy was a predictor of health related behaviour among the nursing students [25].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations